APPLICATION OF LAUNDRY SERVICES AT DWI ANISA LAUNDRY WITH THE APPLICATION OF WEB-BASED WATERFALL METHODS - Ayu Lestari; Ibnu Rasyid Munthe; Marnis Nasution (Jurnal Mantik, 2022)
Many types of businesses currently use information technology media in the form of applications that can facilitate customers and service providers. These applications can help the development of businesses that are run, such as laundry services at Dwi Anisa Laundry, Rantauprapat, which are currently developing and multiplying customers so that the services they run can develop. This built application, created using tools such as VSC, MySQL, and XAMPP as a database with HTML and PHP programming languages, and designed with simple flow and interface design using design methods including context diagram design, data flow diagram, database table structure, and other designing methods, explains the flow of the laundry service management application at Dwi Anisa Laundry Based Web, so that it can be used easily by employees in making transactions, speeding up time, analyzing energy in transaction reports, and reducing the need for laundry service stationery